TRANSFORMASI FILSAFAT PENDIDIKAN ISLAM: MERANCANG STRATEGI INOVATIF PENDIDIKAN MULTIKULTURAL DI ERA REVOLUSI INDUSTRI 4.0 DAN TANTANGAN ABAD 21 - Amin, M.; Haris, Abd (Journal Multicultural of Islamic Education, 2024)
Islamic education faces significant challenges in the era of the Fourth Industrial Revolution, which demands technology-driven innovation. This article examines the role of Islamic educational philosophy in addressing these challenges through an analytical and integrative approach. A literature review is employed to explore the contributions of Islamic educational philosophy to curriculum development, teaching methodologies, and institutional transformation. The findings indicate that Islamic educational philosophy can serve as a conceptual foundation for creating Islamic education that is both relevant and adaptable to contemporary changes while preserving fundamental Islamic values. Transforming Islamic education through inclusive curricula, digital technology, and holistic character-building approaches is identified as a key strategy for fostering progressive Islamic education.